Penerapan Nilai-Nilai Pancasila di Lingkungan Sekolah Menengah Atas dan Kejuruan - Widianti, Viola Rizky; Ramadina Hussain, Kaleda Zia; Nur Hayati, Eka Latifah; Ika Puspita, Ari Metalin (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
In this era of globalization, the application of Pancasila values in the school environment is declining. If left unchecked, the values of Pancasila will be increasingly neglected. This research aims to find out how the implementation of Pancasila values in the school environment. The target of this observation is senior high school, vocational high school, and madrasah aliyah. With a diverse sample, this research can provide a comparison between school types. This research uses a quantitative type approach with data collection through Google Forms. Based on the results and discussion, it shows that students' awareness of the application of Pancasila values is very high, but in implementing it is less than optimal. An active role is needed from the school and teachers to encourage students to practice the values of Pancasila. So that later a sense of unity and integrity will be created in the school environment.